HOW HEALTHY EATING IMPACTS CHILDREN’S DEVELOPMENT (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the significant impact of healthy eating on children’s development, emphasizing the role of nutrition in supporting cognitive, physical, and emotional well-being. By highlighting the importance of healthy eating habits from an early age, parents and caregivers can promote optimal growth and development in children